PENGGUNAAN SPAN 40 SEBAGAI PENYUSUN NIOSOM NATRIUM ASKORBIL FOSFAT DALAM SEDIAAN GEL TERHADAP PENETRASINYA SECARA IN VITRO - ., Veni Lestiawati (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2015)
Sodium ascorbyl phosphate is a hydrophilic compound that is difficult to pass through the stratum corneum. One of the efforts to increase the penetration of the drug through the stratum corneum is to develop in niosome system. This research aims to determine the optimal concentration of span 40 to improve the entrapment efficiency of niosome sodium ascorbyl phosphate that formulated in gel and determine the stability and penetration ability of gel formulas. Concentration of span 40 varied into three formulas: F1 (100 µmol), F2 (150 µmol) and F3 (200 µmol). Gel formulation was made in two formulas used gel base viscolam MAC 10: G1 (sodium ascorbyl phosphate in niosome system) and G2 (sodium ascorbyl phosphate without niosome system). The stability tests performed for 28 days includes organoleptic, pH and determination of levels of sodium ascorbyl phosphate in gel. Penetration test performed by in vitro test using shed snake skin membrane. The result showed F1 formula has an optimum entrapment efficiency were 99,13%±0,099%. G1 formula has the most stable for 28 days of storage than G2 formula. The used of span 40 as niosome composer can be increased penetration of sodium ascorbyl phosphate in gel formulation were 89,04%±0,006%.